An Elephant & Piggie biggie! Volume 3 - Willems, Mo (Willems, Mo. Elephant & Piggie book., 2020)
A collection of five Elephant & Piggie adventures. For the third time ever, best friends Elephant and Piggie have five biggie adventures in one book! Gerald has a bird on his head! Should Piggie swoop in to help? Will rain ruin Gerald and Piggie's fun in the sun? Piggie teachers Gerald how to dance. But what will Piggie learn? Gerald has a big decision to make. Can he make it in time? Gerald is tired and cranky. Will his nap dreams come true?